Economic Impacts of the California One-Variety Cotton Law - Constantine, John H.; Alston, Julian M.; Smith, Vincent H. (Journal of Political Economy, 1994)
The California One-Variety Cotton Law is an important example of technological regulation, in this case intended to serve as a de facto quality control and to mitigate externalities in production that can arise from the mixing of cottonseed at the gin. This paper describes and interprets the economic history of the law, presents a theoretical model of its economic effects, and provides quantitative estimates of the impacts on output, prices, and economic welfare, following a partial deregulation under a 1978 amendment to the law. The analysis shows that large social costs have arisen from concentrating control over the genetic base for California cotton production in the hands of a single government cotton breeder and restricting production to the use of a single selection of a single variety. Some of these costs have been eliminated by the partial deregulation in 1978 to permit private breeders to compete in the provision of genetic material, but production is still restricted to the Acala variety of cotton. While the regulation has benefited some, perhaps even a majority, of the industry participants, it has been increasingly harmful to some other growers and costly overall. The persistence of this costly regulation may be due to the distribution of its impacts: the partial deregulation yielded large increases in aggregate producer surplus but many growers experienced small losses.